Evaluation of Mixture Viscosity Models in the Prediction of Two-phase Flow Pressure Drops - N.Z Aung; T Yuwono (Universitas Gadjah Mada, 2012)
Nine existing mixture viscosity models were tested for predicting a two-phase pressure drop for oil-water flow and refrigerant (R.134a) flow. The predicted data calculated by using these mixture viscosity models were compared with experimental data. Predicted data from using one group of mixture viscosity models had a good agreement with the experimental data for oil-water two-phase flow. Another group of viscosity models was preferable for gas-liquid flow, but these models gave underestimated values with an error of about 50%. A new and more reliable mixture viscosity model was proposed for use in the prediction of pressure drop in gas-liquid two-phase flow.